Some Economic Consequences of the implementation of the Rural Environmental Registry: the case of Municipalities in the Northwest of Rio Grande do Sul (Research, Society and Development, 2020)
The present work seeks to identify some immediate consequences of the implementation of the Rural Environmental Registry. It is a Bill, carried out after several extensions, in the hope that rural producers will adapt to what the legislation established, that is, to register. The first impacts identified in the application of the Law, for those who did not register their rural properties, came in the form of negative agricultural financing, a requirement pointed out by bank agencies, as well as the non-authorization of contracting agricultural insurance. To verify the consequences, a methodological approach relies on qualitative research, semi-structured interviews, with professionals who work directly with rural producers and who are familiar with the Environmental Registry. This process contributed to a better understanding of the problems faced by rural producers, when the Registration was carried out or not. The results of the research indicate that rural properties will have profound losses in their revenues, as a result of the implementation of the Register, especially in the reduction of planted areas. On the other hand, sustainable and rational use of existing natural resources will imply a reduction in air, water and soil pollution, preservation of biodiversity, which should favor the socioeconomic development of future generations.